2012
DOI: 10.1038/jp.2012.44
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral amino acid intakes: possible influences of higher intakes on growth and bone status in preterm infants

Abstract: Early higher AA intakes improved growth without short-term AA intolerance. Nutritional parameters could influence bone growth. LLL was the anthropometric parameter that best correlated to bone status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 36 publications
1
25
0
1
Order By: Relevance
“…Vlaardingerbroek et al [13], Clark et al [16], and Blanco et al [33,34,35] reported mean weight gain for the first 28 days, Burattini et al [24] compared mean weight gain at 36 weeks postmenstrual age (PMA), and Bellagamba et al [23] reported mean weight gain rates from birth and regain of BW to 1,800 g (54 days in both groups). Scattolin et al [26] also reported growth rates, but only for the 2nd and 3rd week of life separately and was, therefore, not included in the meta-analysis. They described a higher growth rate in the intervention group that became significant in the 3rd week of life (18.76 [SD 6.83] vs. 14.70 [SD 8.99] g/kg/day, p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vlaardingerbroek et al [13], Clark et al [16], and Blanco et al [33,34,35] reported mean weight gain for the first 28 days, Burattini et al [24] compared mean weight gain at 36 weeks postmenstrual age (PMA), and Bellagamba et al [23] reported mean weight gain rates from birth and regain of BW to 1,800 g (54 days in both groups). Scattolin et al [26] also reported growth rates, but only for the 2nd and 3rd week of life separately and was, therefore, not included in the meta-analysis. They described a higher growth rate in the intervention group that became significant in the 3rd week of life (18.76 [SD 6.83] vs. 14.70 [SD 8.99] g/kg/day, p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis was not possible due to a lack of consistency in the timeline, but none of the individual studies found a significant difference in head growth rate between groups. Mean HC per group at 36 weeks PMA was described in 5 studies [23,24,25,26,27]. All 5 studies indicated no difference in HC at birth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether this trend persists into childhood is not known. Using bone transmission time, Scattolin et al found protein intake to positively correlate with bone mineral status at 36 wk postmenstrual age (60). However, Fewtrell was unable to correlate protein intake in infancy with peak bone mass or bone turnover in young adulthood (36).…”
Section: The Role Of Dietary Proteins In Growth and Body Compositionmentioning
confidence: 99%
“…These studies report improved absolute and standardized measures of weight, length and head circumference as well as an increased growth velocity. No intolerance of high-protein diets has been reported (52,60) and glycaemic control might actually be improved with a high protein intake (53,54). However, protein intake in the neonatal period will not necessarily have an impact on growth indices in childhood (59).…”
Section: The Role Of Dietary Proteins In Growth and Body Compositionmentioning
confidence: 99%